The life experience of families concerning the work of the mental health professionals: a phenomenological study - Marcio Wagner Camatta; Jacó Fernando Schneider (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
This study aims at understanding the life experience of family members of users from a Psychosocial Attention Center concerning the work of the mental health professionals. It's a qualitative research, based on Alfred Schutz' Social Phenomenology framework. Data were collected through interviews with 13 family members in 2006 at a mental health service in Porto Alegre, Brazil. The comprehensive analysis allowed to consider that the social relationship face-to-face, among families and mental health team, permits the professional closer the existential dimension of families, identifying their specific needs. This relationship has increased the proximity among the families, professionals and users. However, the team actions should also consider others socials areas to exercise citizenship continuously. The involvement of families in team work is essential to reach durable and self-sustaining results in mental health attention.